Language skills in cypriot-greek speaking toddlers with specific language delay - Petinou, Kakia; Constantinou, Astero; Kapsou, Margarita (My University, 2011)
The current investigation examined longitudinally the emergence of specific linguistic parameters in toddlers with and without late onset of expressive language. The central aim of this investigation was to compare the linguistic skills of typically developing and late-talking toddlers while: (a) observing patterns of linguistic development between the two groups on specific parameters and (b) examining the impact of early language delay on language-specific parameters and comparing these with cross-linguistic data. The subjects were 18 Cypriot-Greek speaking toddlers classified as late-talkers (LTs), and 18 age-matched counterparts with normal course of language development (NLDs). Participants were assessed at 28 months, 32 months, and 36 months, using various linguistic measures such as receptive and expressive vocabulary, mean length of utterance as measured in words (MLU-W), and phonetic production. Overall, the two groups exhibited parallel developmental profiles, with a language lag favoring the LT group as compared to the NLD counterpart. The results of this study highlight the negative effect of early language delay on later language skills, even up to age three years and lend support to the current literature regarding the universal linguistic picture of early and persistent language delay. Finally, the findings are discussed in view of the need for further research with a focus on more language sensitive tools in testing later language outcomes. © 2011 Koninklijke Brill NV, Leiden.
Keywords: Cypriot-greek; Late-talkers; Mean length of utterance; Specific language delay; Toddlers